PENERAPAN MODEL PEMBELAJARAN THINK PAIR SHARE (TPS) BERBASIS MODEL LATIHAN INKUIRI UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF - Primadya Anantyarta (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2016)
Pre-research learning observations in SMP Satu Atap Merjosari, VII Class C indicates that students have low cognitive learning outcomes. 17 students have cognitive value meets the Criteria Complete Minimal value of the number of 38 students on the 1st midterm. One reason is the application of learning models are lacking. Low concentration of students in the study can hinder the process of understanding a concept. Students don’t have the opportunity to build their own knowledge, thus causing students get low cognitive learning outcomes. Application of learning model Think Pair Share trains students to work independently and in pairs, which can help improve the learning process. Inquiry Training Model are also needed to help students build their own knowledge, so the application of harmony between the Think Pair Share learning model and inquiry training model learning is expected to increase students' cognitive learning outcomes. Class Action Research is composed of two cycles and has a phase Planning, Implementation, observation, and reflection. The experiment was conducted in May to June 2010. The research instrument used held observation sheet learning and test questions each end of the cycle in the study. The results showed that the average score of classical students in the first cycle of 77.5 increased in the second cycle becomes 82.4. Classical completeness increased from 79 became 94.7. This indicates that the application of the Think Pair Share learning model based inquiry training model can improve cognitive learning outcomes of students.